A New annotated checklist of the Portuguese oaks (Quercus L., Fagaceae) - Vila-Viçosa, Carlos Martins; Capelo, Jorge Henrique; Alves, Paulo; Almeida, Rubim Silva; Vázquez, Francisco Maria (Mediterranean Botany, 2023)
We present a comprehensive taxonomic and nomenclatural review of the Portuguese oaks (Quercus L.), issuing from thorough biogeographical, historical, bibliographic, field and herbarium data. We propose a new annotated checklist for all taxa and nothotaxa belonging to Quercus L. genus in the Portuguese national territory, extending the analysis to the broader biogeographical context of the Western Mediterranean subregion. Fifteen herbaria collections were exhaustively studied and complemented by information retrieved from digital collections, resulting in the recognition of eleven native oaks. Further treatment at infraspecific level includes one subspecies and additional 23 nothotaxa. We designate lectotypes for 27 names and add a preliminary list of 149 cultivated taxa, resulting in a total of 184 oaks found in Portugal. Moreover, we clarify the taxonomical status and reinstate Q. pseudococcifera and Q. airensis as native to the western Mediterranean subregion. We recover the concept of Q. faginea, as the widespread gall oak in Portugal and update its synonym list. We propose Q. orocantabrica and Q. estremadurensis as autonomous species within the broad European Q. robur s.l. group, alongside two newly circumscribed subsections within Section Quercus. We describe five new nothotaxa, including four unreported to nature and one missing a suitable name (Q. ×almeidae, Q. ×alvesii, Q. ×capeloana, Q. ×eborense and Q. ×sampaioana) and we approach the nomenclatural resolution of the remaining natural hybrids. Lastly, we provide an identification key, intelligible for non-specialists, including both native taxa and most frequent nothotaxa. We emphasise the importance of historical and literature review, combined with accurate biogeographical information, as paramount to coherent taxonomical resolution. Both specimens and their associated records were found of crucial significance to a taxonomical model that is, in the end, useful for biodiversity conservation.